Business hack : the wealth dragon way to build a successful business in the digital age - Lee, John, 1981- (John Wiley & Sons Ltd., 2019)
"Master the online tools available to grow your business and conquer the competition Business Hack is your essential roadmap to business growth and online marketing success. Author and successful entrepreneur John Lee shares his proven methods to harness the power of online tools, including using social mediaoffering practical steps to create and implement highly effective cyber-marketing campaigns. Thanks to the digital revolution, you no longer need teams of marketing experts and other expensive overheads to build and promote your business. This unique and valuable resource covers everything you need to consider when building your marketing strategy, from established principles of sales to cutting-edge digital techniques. In todays dynamic business environment, strong and ongoing engagement in social media marketing is no longer an optionit is a necessity. From local craft-based businesses to new tech start-ups and even global multinational corporations, effective cyber-marketing can be instrumental in determining success. A comprehensive digital strategy enables you to compete across all platforms and maintain viability and relevance in the face of intense competition. Following the proven techniques in this essential guide allows you to: Implement powerful social media marketing campaigns to increase revenue and rise above the competition Integrate traditional sales and advertising methods with modern technology to create a comprehensive business marketing strategy Identify future trends to stay ahead of the technology curve and capitalize on new opportunities. Learn the skills used by successful entrepreneurs and respected experts in online marketing The Internet and rise of digital media have changed the rules of business and marketing. It is now possible for small and new businesses to compete and thrive in the global marketplace through intelligent use of digital and social media marketing. Business Hack provides the tools and knowledge necessary to succeed in the 21st century."--